(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
Although Artificial Intelligence (AI)-based recruitment systems are increasingly being used, the lack of algorithmic transparency in the decision-making process can raise doubts and reduce employee trust in the selection results. This study aims to examine the effect of algorithmic transparency on employee trust in AI-based recruitment systems. The study used a quantitative approach with a survey method, distributing questionnaires to respondents with experience and knowledge of AI-based recruitment processes. Data were analyzed using statistical techniques to examine the relationship between algorithmic transparency and employee trust. The results showed that algorithmic transparency had a positive and significant effect on employee trust. The more transparent information regarding the system’s working mechanisms, assessment indicators, and AI decision-making processes, the higher the level of employee trust in the system. These findings suggest that transparency is an important factor in improving perceptions of fairness, reducing uncertainty, and strengthening the acceptance of AI technology in the recruitment process.